Association between grip strength level and fall experience among older Chinese adults: a cross-sectional study from the CHARLS - Gengxin Dong; Yuxin Guo; Ji Tu; Yunqing Zhang; Huaze Zhu; Dapeng Bao; Junhong Zhou (BMC Geriatrics)
Abstract Objectives To explore the dose-response relationship between levels of grip strength and the fall experience among older adult Chinese. Methods This study used data from the 2015 China Health and Retirement Longitudinal Study (CHARLS), including 5,486 older Chinese adults aged 60 and above. Grip strength was measured with a dynamometer, and falls were recorded via questionnaire. Logistic regression and restricted cubic spline (RCS) tests assessed the relationship between grip strength and fall experience. Additionally, disparities across different genders, age, and residential areas were explored. Results After adjusting for confounding factors, compared to the lowest quartile of grip strength, the fall experience of older men decreased by 39% (OR = 0.61, 95% CI = 0.45–0.84, p = 0.002) in the third quartile and 42% (OR = 0.58, 95% CI = 0.42–0.80, p < 0.001) in the highest quartile, the fall experience of older women decreased by 33% (OR = 0.67, 95% CI = 0.51–0.88, p = 0.004) in highest quartile. Restricted cubic spline analysis indicated a negative dose-response relationship between grip strength levels and fall experience among older Chinese adults. Subgroup analyses revealed that the negative dose - response relationship between grip strength levels and fall experience was absent among the elderly aged 75 and above, as well as among rural - dwelling females. Conclusion This cross-sectional study utilizing CHARLS data reveals a significant negative dose-response relationship between grip strength and falls among Chinese older adults aged 60 to 75 years living in urban areas and Chinese older men of the same age group residing in rural areas. Within this demographic, grip strength can be preliminarily used to estimate the likelihood of falls, enabling the early implementation of preventive interventions to reduce the personal and societal impacts associated with fall-related injuries. Clinical trial number Not applicable.